Poly(ADP-ribose): From chemical synthesis to drug design. Issue 15 (1st August 2016) - Drenichev, Mikhail S.; Mikhailov, Sergey N.
Graphical abstract: Abstract: Poly(ADP-ribose) (PAR) is an important biopolymer, which is involved in various life processes such as DNA repair and replication, modulation of chromatin structure, transcription, cell differentiation, and in pathogenesis of various diseases such as cancer, diabetes, ischemia and inflammations. PAR is the most electronegative biopolymer and this property is essential for its binding with a wide range of proteins. Understanding of PAR functions in cell on molecular level requires chemical synthesis of regular PAR oligomers. Recently developed methodologies for chemical synthesis of PAR oligomers, will facilitate the study of various cellular processes, involving PAR.